2005
DOI: 10.1128/jb.187.22.7619-7630.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Visualization ofPseudomonas aeruginosaPAO1 Biofilms by Freeze-Substitution Transmission Electron Microscopy

Abstract: High-pressure freeze-substitution and transmission electron microscopy have been used for high-resolution imaging of the natural structure of a gram-negative biofilm. Unlike more conventional embedding techniques, this method confirms many of the observations seen by confocal microscopy but with finer structural detail. It further reveals that there is a structural complexity to biofilms at both the cellular and extracellular matrix levels that has not been seen before. Different domains of healthy and lysed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
77
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 66 publications
3
77
0
Order By: Relevance
“…These may in turn interact to form higher-order structures, e.g., lattices of intertwined molecules, or particulate structures such as pili (fimbriae), flagella, phage, and membrane vesicles (MVs), all of which have been reported within biofilms (8,10,18,21,27,38,57,62). Yet, in spite of the tremendous effort to understand the contribution of matrix chemistry to matrix properties, our current knowledge of the ultrastructure of the matrix is still limited (32).…”
mentioning
confidence: 99%
“…These may in turn interact to form higher-order structures, e.g., lattices of intertwined molecules, or particulate structures such as pili (fimbriae), flagella, phage, and membrane vesicles (MVs), all of which have been reported within biofilms (8,10,18,21,27,38,57,62). Yet, in spite of the tremendous effort to understand the contribution of matrix chemistry to matrix properties, our current knowledge of the ultrastructure of the matrix is still limited (32).…”
mentioning
confidence: 99%
“…While a variety of biofilms have been studied in depth by optical imaging approaches, only a few have been faithfully preserved and visualized at high resolution by transmission electron microscopy (3,22,25,26,45,48,49). A recent ultrastructural study of Pseudomonas aeruginosa biofilms shows that high-pressure freezing/freeze-substitution results in superior preservation (22).…”
mentioning
confidence: 99%
“…Bacteria in biofilms exhibit protein expression patterns different from those of planktonic bacteria (41). Within a biofilm, bacteria are typically embedded in an extracellular polymeric substance (EPS) matrix (7,17,43) that protects the microbial community members from desiccation, from phagocytosis, and, in the case of human pathogens, from the host immune system (8).While a variety of biofilms have been studied in depth by optical imaging approaches, only a few have been faithfully preserved and visualized at high resolution by transmission electron microscopy (3,22,25,26,45,48,49). A recent ultrastructural study of Pseudomonas aeruginosa biofilms shows that high-pressure freezing/freeze-substitution results in superior preservation (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cell envelope was visibly affected, with undulations of the outer membrane giving the periplasm an irregular appearance. It has been suggested that traditional techniques of specimen preparation for TEM can induce features such as membrane artifacts and the condensing of cytoplasmic material (Hunter & Beveridge, 2005). Some of the artifacts previously described include irregular width of the periplasmic space, poorly defined plasma membrane and undulations of the cell envelope (Hobot et al, 1984).…”
Section: Discussionmentioning
confidence: 99%